Potentials and Problems of Agricultural Development in Dhading District - Pathak, Ram Sharan (NUTA Journal, 2019)
The cereal crops, cash crops and pulses are mainly grown in Dhading district owing to variations in topography and climate. Cereal crops are most dominant crops in the district in terms of area under cultivation and production. Cereal crops account for 93 percent of the cultivated land and 78 percent of the total crop production. In this context, this paper tried to analyze potentials and problems of agriculture development in Dhading District. To the end, the study purposively selected six settlements from total 216 settlements located around Thopal Khola drainage basin of central Dhading. Three factors (i.e. distance from the district headquarter, different forms of transportation which affect in different ways on the agricultural transformation and terrain, such as river valley and ridge area providing different base to agricultural development) were taken into consideration while selecting those settlements. Primary data were collected from 132 farm households, ranging from 20 households from small villages to 24 households from large villages. The study found that farmers were well aware about their concern with return against the investment from agricultural crops, which are yet determined more by natural factors than infrasturcture and facilities. Therefore, the agricultural development policies and programmers require mitigating adverse impacts of natural factors by providing and strengthening the facilities and services such as irrigation, road access, service centres, supply of agricultural inputs, market demand links, etc, ensuring their long term impacts.